Factors associated with current tobacco use among adolescents and young students - Samara Barreto Cunha; Rodrigo Cappato de Araújo; Jéssica Vanessa Barros de Oliveira; Rachel Mola; Ana Carolina Rodarti Pitangui (Brazilian Society of Pediatrics, 2020)
Objectives: To determine the prevalence of current tobacco use and its association with sociodemographic factors and risk behaviors among adolescents and young students, according to gender. Methods: The sample consisted of students from the state public school network aged between 12 and 24 years, who answered the Brazilian version of the Youth Risk Behavior Survey questionnaire. The data were analyzed in SPSS software (v. 20.0), using Poisson regression to evaluate the prevalence ratio (PR) of the independent variables in relation to the outcome. p < 0.05 was established as the significance level. Results: The final analysis consisted of 1275 adolescents, of whom 716 (56.2%) were girls and 559 (43.8%) were boys. The prevalence of current tobacco use was 6.6% among girls and 9.7% among boys. In females, consuming alcohol in the last 30 days (3.91 [1.54-9.94]) and being 14 years old or younger (0.50 [0.26-0.96]) influenced current tobacco use. In the male gender, tobacco use in the last 30 days was influenced by current alcohol consumption (2.92 [1.21-7.08]) and involvement in physical fighting in the last 12 months (2.32 [1.32-4.09]). Conclusion: Although the prevalence of current tobacco use was low in both genders, the assessed population still presents a risk, since male involvement in physical fighting and current consumption of alcohol in both genders increased the probability of this population becoming regular tobacco users. Resumo: Objetivos: Determinar a prevalência de uso atual do tabaco e sua associação com fatores sociodemográficos e comportamentos de risco entre adolescentes e jovens escolares, segundo o sexo. Métodos: A amostra foi composta por estudantes da rede estadual entre 12 e 24 anos, que responderam a versão brasileira do questionário Youth Risk Behavior Survey. Os dados foram analisados no SPSS (versão 20.0), por meio da Regressão de Poisson para avaliar a Razão de Prevalência (RP) das variáveis independentes em relação ao desfecho. Foi adotado p < 0,05. Resultados: A análise final foi composta por 1.275 adolescentes, dos quais 716 (56,2%) eram meninas e 559 (43,8%) meninos. A prevalência de consumo atual do tabaco foi de 6,6% entre as meninas e 9,7% entre os meninos. No sexo feminino, consumir álcool nos últimos 30 dias (3,91 [1,54-9,94]) e ter 14 anos ou menos (0,50 [0,26-0,96]) influenciaram o uso atual de tabaco. No sexo masculino, o uso de tabaco nos últimos 30 dias foi influenciado pelo consumo atual de álcool (2,92 [1,21-7,08]) e envolvimento em luta corporal nos últimos 12 meses (2,32 [1,32-4,09]). Conclusão: Embora a prevalência de consumo atual do tabaco tenha sido baixa em ambos os sexos, a população estudada ainda exibe risco, pois o envolvimento em luta corporal no sexo masculino e o consumo atual de álcool em ambos os sexos aumentaram a probabilidade da população se envolver com uso atual do tabaco.